1999
DOI: 10.1152/jn.1999.82.1.330
|View full text |Cite
|
Sign up to set email alerts
|

Responses to Auditory Stimuli in Macaque Lateral Intraparietal Area I. Effects of Training

Abstract: The lateral intraparietal area (LIP) of macaques has been considered unresponsive to auditory stimulation. Recent reports, however, indicate that neurons in this area respond to auditory stimuli in the context of an auditory-saccade task. Is this difference in auditory responsiveness of LIP due to auditory-saccade training? To address this issue, LIP responses in two monkeys were recorded at two different times: before and after auditory-saccade training. Before auditory-saccade training, the animals had never… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
86
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 47 publications
16
86
0
Order By: Relevance
“…This is consistent with the idea that neural networks of the posterior association cortices specialize in particular modalities or aspects of sensory information (Fuster 2001;Fuster 2004). The activity of cells in the posterior parietal cortex (PPC) was shown to be correlated with working memory (Koch and Fuster, 1989;Quintana and Fuster, 1993;Iriki et al, 1996;Grunewald et al, 1999;Linden et al, 1999;Burton and Sinclair, 2000;Snyder et al, 2000;Andersen and Buneo, 2002;Pesaran et al, 2002;Constantinidis and Procyk, 2004). PPC was also shown in human imaging studies to be involved in crossmodal transfer of information between the tactile and visual representations (Hadjikhani and Roland, 1998;Saito et al, 2003).…”
Section: Erp Componentssupporting
confidence: 78%
“…This is consistent with the idea that neural networks of the posterior association cortices specialize in particular modalities or aspects of sensory information (Fuster 2001;Fuster 2004). The activity of cells in the posterior parietal cortex (PPC) was shown to be correlated with working memory (Koch and Fuster, 1989;Quintana and Fuster, 1993;Iriki et al, 1996;Grunewald et al, 1999;Linden et al, 1999;Burton and Sinclair, 2000;Snyder et al, 2000;Andersen and Buneo, 2002;Pesaran et al, 2002;Constantinidis and Procyk, 2004). PPC was also shown in human imaging studies to be involved in crossmodal transfer of information between the tactile and visual representations (Hadjikhani and Roland, 1998;Saito et al, 2003).…”
Section: Erp Componentssupporting
confidence: 78%
“…It is impossible to compare our results with those of Grunewald et al (1999) because they showed little behavioral data. Nevertheless, they reported that after extensive training, which included specific visual feedback, their monkeys could perform a localization task that included only two targets located at (Ϯ16°, 8°) with acceptance windows 32°in diameter.…”
Section: Comparison With Previous Studiesmentioning
confidence: 86%
“…However, it is presently unclear whether the species can actually localize sound sources. For instance, Grunewald et al (1999) reported that monkeys could not make saccadic eye movements to the sources of sounds in the context of a simple saccade task. In a companion study performed in the same monkeys used by Grunewald et al (1999), Linden et al (1999) only presented acoustic targets from two locations, one on each side of the midline, an experimental task that hardly required sound localization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, the amount of research about audition using this approach is scant (5). Most of the studies in the auditory cortex and related areas have described the response properties of neurons to auditory scenes in anesthetized and awake animals, and how these are affected by different task conditions (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). But how the neural representations of acoustic stimuli are related to perception, memory and decision making is not known.…”
mentioning
confidence: 99%